Analysis of the physicochemical quality of raw milk delivered to a processing cooperative in the city of Juína-MT (Research, Society and Development, 2022)
The quality of raw milk for the processing industry is directly linked to the characteristics of its final product. Thus, raw milk as a raw material both for the processing of fluid milk and for the production of derivatives must present good physicochemical, microbiological, and sensory characteristics, for this reason, it is essential that industries carry out evaluations for control quality and fraud investigation. This study aimed to evaluate, through physical-chemical and fraud analysis, the quality of raw milk delivered to a processing cooperative in the city of Juína-MT, in order to verify compliance with the parameters determined by current legislation. The results indicated that the average contents of proteins, lactose, total solids, non-fat solids, density, and titratable acidity were within the values established by the recommended by IN 62 of the MAPA for milk. However, the fat and cryoscopy contents varied, being mostly averages below the established minimum value. In determining the temperature, all means were outside the established standard, this was due to the fact that the producers delivered the milk in cans, without any type of refrigeration. The alizarol test was positive in nine samples and the diaper search was also positive for the addition of hydrogen peroxide in two samples and no sample was positive for the addition of starch, results that were not very expressive in relation to the 188 samples analyzed. In general, it is concluded that the raw milk received by the cooperative located in the city of Juína-MT presented good physicochemical quality.